An Investigation into the Educational Philosophy and Spirituality of Iranian EFL Teachers - Elaheh Suleimani; Rahman Sahragard (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2016)
Although philosophy and spirituality are related to various branches of disciplines, they have not been subject to focused attention in foreign language teaching. In this paper, schools of educational philosophy, and spirituality in education were connected together to present the stance, viewpoint, and practice of these two constructs in English as foreign language (EFL) Iranian educators. Results indicated that the dominant philosophy of education of Iranian EFL teachers was progressive education. Furthermore, combination of progressive and humanistic philosophies and humanistic philosophy were to some extent established a balance with progressivism. None of the participants practice spirituality in classrooms. By illuminating the spiritual language of humanistic and progressive philosophies, we may conclude that the nature and spiritual discourse of each philosophy as well as their practical implications should be articulated in teacher education programs to fulfill the everlasting growth of an individual as an utmost purpose of education.